Danggui-Shaoyao-San Improves Gut Microbia Dysbiosis and Hepatic Lipid Homeostasis in Fructose-Fed Rats - Yin, Jing; Lu, Jiaxi; Lei, Peng; He, Mingshuai; Huang, Shengjie; Lv, Jialin; Zhu, Yan; Liu, Zhidong; Jiang, Miaomiao (Frontiers in Pharmacology, 2021)
Metabolic syndrome (MetS) is a pathological state of many abnormal metabolic sections. These abnormalities are closely related to diabetes, heart pathologies and other vascular diseases. Danggui-Shaoyao-San (DSS) is a traditional Chinese medicine formula that has been used as a therapy for Alzheimer's disease. DSS has rarely been reported in the application of MetS and its mechanism of how it improves gut microbia dysbiosis and hepatic lipid homeostasis. In this study, three extracts of DSS were obtained using water, 50% methanol in water and methanol as extracting solvents. Their chemical substances were analyzed by ultra-performance liquid chromatography coupled with quadrupole time-of-flight mass (UPLC-Q/TOF-MS). Pharmacodynamic effect of the extracts were evaluated by comparison of biochemical factors, 16S rRNA sequencing test for gut microbiota analysis, as well as metabonomic and transcriptomic assessments on liver tissues from fructose-fed rats. This study aimed at investigating DSS’s mechanism of regulating blood lipid, anti-inflammation and reducing blood glucose. The results showed that the 50% methanol extract (HME) was more effective. It was worth noting that hydroxysteroid 17β-dehydrogenase 13 (HSD17β13) as a critical element of increasing blood lipid biomarker-triglyceride (TG), was decreased markedly by DSS. The influence from upgraded hydroxysteroid 17β-dehydrogenase 7 (HSD17β7) may be stronger than that from downgraded Lactobacillus in the aspect of regulating back blood lipid biomarker-total cholesterol (TC). The differential down-regulation of tumornecrosis factor alpha (TNF-α) and the significant up-regulation of Akkermansia showed the effective effect of anti-inflammation by DSS. The declining glycine and alanine induced the lowering glucose and lactate. It demonstrated that DSS slowed down the reaction of gluconeogenesis to reduce the blood glucose. The results demonstrated that DSS improved pathological symptoms of MetS and some special biochemical factors in three aspects by better regulating intestinal floras and improving hepatic gene expressions and metabolites.